Presence of medium-sized mammals in a fragment of tropical forest on the banks of the Bacalar Lagoon, Quintana Roo - Sánchez-Zavalegui, Romeo Alejandro; Cimé-Ruiz, María Marcela; Tuz-Catzin, Carlos (Therya Notes, 2024)
Faunal research is crucial in wildlife and ecosystem conservation studies. In the case of Bacalar, research on local wildlife is scarce. This study aimed to identify the presence of wild mammals in a fragment of semi-preserved forest associated with the Bacalar Lagoon. The study was carried out over the period 2022–2023. Systematic sampling included direct observations along transects 1 km long by 2 m wide during daytime (7:00 hr) and nighttime (20:00 hr) routes and through photo-trapping with 10 camera traps installed in strategic areas (wildlife trails, watering holes, and periphery of fruit trees). The presence of 12 species of wild mammals belonging to 6 orders and 9 families was recorded, highlighting the order Carnivora with 4 species. A second record of Potos flavus (martucha) was obtained in Bacalar, and also recorded were Herpailurus yagouaroundi (jaguarundi) and Leopardus wiedii (ocelot), scarcely documented in the area. Eight of the 12 reported species were observed in the dry season (May-August). The richness of predators of the order Carnivora is attributed to the good state of conservation of the study area and the presence of prey. In addition, the increase in records during the dry season may be related to the Bacalar Lagoon as a water source. This paper highlights the importance of local fauna studies and the need for further studies of wild mammals in the state of Quintana Roo.